Negotiating psychological costs: How welfare recipients' perceived interactions with welfare bureaucrats impact their experiences of administrative burden - Raab, Miriam (International Journal of Social Welfare, 2025)
While it is well established that welfare bureaucrats hold some discretionary power in implementing welfare policies, scholars of the administrative burden concept have only recently begun to consider their individual impacts on welfare recipients' experiences of onerous state encounters. This article aims to explore how welfare recipients' perceptions of personal interactions with welfare bureaucrats shape their experiences of administrative burden, specifically their psychological costs, by drawing on biographical–narrative interviews conducted with 33 (former) welfare benefit recipients in Germany. The results reveal that welfare recipients perceive individual welfare bureaucrats as responsible for reducing, increasing, or creating certain psychological costs they experience and that welfare recipients themselves respond to these costs and negotiate them to some extent. This article contributes to the growing literature on citizens' experiences of administrative burden and expands the concepts of psychological costs and citizen agency by building on theoretical frameworks of coping behaviours in response to stress and psychological costs. The results also confirm a need for policy changes that support, rather than discourage, more case-sensitive approaches to welfare benefits and employment services.
CRIS-Team Scopus Importer:2025-05-16
Keywords: administrative burden; citizen agency; psychological costs; welfare recipients